Mexican Brand Insect Fluid Label (1910)
Printed bottle label for Mexican Brand Insect Fluid, depicting a woman using the product in a bedroom, with the tagline "What is Home without a Clean Bed."
Keywords: Public health; DDT (Insecticide); Insecticides; Toxins